2023
DOI: 10.1002/ldr.4609
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the Grain‐for‐Green Program and check dams increased vegetation carbon sequestration in the Yanhe basin, Loess Plateau

Abstract: Vegetation carbon sequestration, usually expressed by net primary production (NPP), is an important ecosystem service (ES) to mitigate global warming. Multiple soil and water conservation projects (SWCPs) have been implemented to restore disturbed ecosystems on the Loess Plateau (LP), as one of the most eroded areas in the world.However, responses of NPP to the conservation projects are unclear due to trade-offs between NPP and other ESs. Herein, we quantified NPP and other key ESs (i.e., water yield, soil con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Since the InVEST model includes LULC data as a necessary input parameter, ESs also changed with LULC variation. Overall, HQ, WC, and SC in the Beichuan River Basin were improved under the GFGP project, while NPP and WS decreased, which was consistent with previous studies (Figure 3 and Table 4) (Aneseyee et al, 2020; Xue et al, 2022; Yan et al, 2022; Zhang et al, 2023). It is a generally accepted view that a decrease in cropland and an increase in forest can improve HQ (Vellend, 2004; Zermeno‐Hernandez et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Since the InVEST model includes LULC data as a necessary input parameter, ESs also changed with LULC variation. Overall, HQ, WC, and SC in the Beichuan River Basin were improved under the GFGP project, while NPP and WS decreased, which was consistent with previous studies (Figure 3 and Table 4) (Aneseyee et al, 2020; Xue et al, 2022; Yan et al, 2022; Zhang et al, 2023). It is a generally accepted view that a decrease in cropland and an increase in forest can improve HQ (Vellend, 2004; Zermeno‐Hernandez et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…The decrease in cropland and shrubland was not equated with the increase in forest and grassland, where a large amount of shrubland was degraded to grassland, while some grassland was converted to barren and urban land. In addition, the conversion of most cropland to grassland forced the local population to shift their economic resources from crop cultivation to grazing, thus negatively affecting most of the grasslands with potentially high NPP, which was responsible for the slight decrease in NPP in 2020 compared to that in 2000 (Table 4) (Zhang et al, 2023) infiltration capacity of soils, thus indirectly influencing the WC function (Sun et al, 2018). Forest restoration projects greatly improve soil infiltration capacity and SC services by promoting the conversion of cropland and shrubland to forest (Qi et al, 2019).…”
Section: Lis Contagion Indexmentioning
confidence: 99%
“…Engineering works such as silt dams and terraces, and biological management measures such as afforestation, have alternated over the past 60 years in the Loess Plateau of China and are gradually moving towards the development stage of a comprehensive combination of engineering and biological management [34]. In other regions, these engineering works have also been shown to affect ecological processes, which in turn affect changes in ecosystem services and ESRs [14,35] GGP is a typical example of ecological compensation, a massive vegetation restoration initiative that the Chinese government has been carrying out since 1999, which is the biggest ecological restoration project in the world in terms of size and funding [36,37]. It has been implemented mainly in the Beiniu River basin and Gushan River basin in Fugu County, with a small number of sporadic distributions in the Huangfu River basin and Qingshui River basin as well.…”
Section: Ecological Restoration Project Impacts Trade-offs and Synerg...mentioning
confidence: 99%
“…Different ecological restoration measures may have different impacts on ecosystem services as well as ESRs. For example, in Zhang et al's study, ecological restoration projects were shown to improve greening and stewardship services, which have a positive impact on enhancing ecosystem services; however, it was underlined that greening exacerbates trade-offs between socioecological systems in degraded ecoregions [14]. Pan et al's study, assessing and comparing the impacts of tree plantations and primary forests, demonstrated that ecological restoration projects may not only enhance ecosystem services, but may also bring about some environmental and social trade-offs [15].…”
Section: Introductionmentioning
confidence: 99%
“… 27 Much like the role of ecological construction in reducing carbon emissions, 28 studies supporting the promotion of carbon stock through dams argue that dams can stimulate the regeneration of vegetation on unoccupied lands. 29 , 30 This process involves the absorption of carbon dioxide from the atmosphere through photosynthesis, leading to the storage of carbon in various forms, including biomass (such as trunks, branches, roots, and leaves), dead organic matter (litter and dead wood), and soil. 31 , 32 However, other studies posit that the increased availability of water resources resulting from dam construction can encourage the expansion of both cropland and built-up areas to a certain extent.…”
Section: Introductionmentioning
confidence: 99%